The Intensity Recognition of Tension Emotion Based on Multi- physiological Signals. Issue 5 (2016) - Zhou, Peng; Qi, Hongzhi; Liu, Mengting; Wei, Jinwen; He, Feng; Liu, Shuang; Wang, Xuemin; Meng, Jiayuan; Scott, Mattew; An, Xingwei; Ming, Dong
No abstract available